Calculate of Electromagnetic Transition for 122Te Isotope - Al_Shareefi, Mohammed Abdul Amir kareem; Aldalawi, Ali Adil Turki (Al-Qadisiyah Journal of Pure Science, 2018)
In this research, the properties of energy levels for even-even 122Te isotope and electric quadruple moments Q21+have been studies by using (IBM) Hamiltonian. the experimental data compared with the Previous work. It is found that the 122Te Isotops has value agreement with experimental data. And this nuclei have the properties of U(5) to Su(3) transition region .According to (IBM), 122Te isotope have been shown their membership to the transition region SU(5)-O(6).